2012
DOI: 10.1371/journal.pone.0049322
|View full text |Cite
|
Sign up to set email alerts
|

The Co-Chaperone Hch1 Regulates Hsp90 Function Differently than Its Homologue Aha1 and Confers Sensitivity to Yeast to the Hsp90 Inhibitor NVP-AUY922

Abstract: Hsp90 is a dimeric ATPase responsible for the activation or maturation of a specific set of substrate proteins termed ‘clients’. This molecular chaperone acts in the context of a structurally dynamic and highly regulated cycle involving ATP, co-chaperone proteins and clients. Co-chaperone proteins regulate conformational transitions that may be impaired in mutant forms of Hsp90. We report here that the in vivo impairment of commonly studied Hsp90 variants harbouring the G313S or A587T mutation are exacerbated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 61 publications
3
52
0
2
Order By: Relevance
“…However, previous studies showed that cells that lack nonessential co-chaperones exhibit growth defects in cells expressing mutant Hsp90 (21,44). We compared the growth of a panel of Hsp90 temperature-sensitive mutants in WT (JJ816) or ⌬cpr6 (JJ110) cells that lacked chromosomal Hsp90 genes.…”
Section: The Tpr Domain Of Cpr6mentioning
confidence: 99%
“…However, previous studies showed that cells that lack nonessential co-chaperones exhibit growth defects in cells expressing mutant Hsp90 (21,44). We compared the growth of a panel of Hsp90 temperature-sensitive mutants in WT (JJ816) or ⌬cpr6 (JJ110) cells that lacked chromosomal Hsp90 genes.…”
Section: The Tpr Domain Of Cpr6mentioning
confidence: 99%
“…First, due to the large structural rearrangements involved upon inhibitor association, the contribution from regions other than the nucleotide-binding pocket can be quite substantial and hard to predict by analyzing the structure alone. Second, the cellular effects of Hsp90 inhibitors are related to the conformational limitations imposed on the chaperone, affecting co-chaperone binding and long-range coupled motions observed between the NTD and CTD domains [64].…”
Section: Discussionmentioning
confidence: 99%
“…We propose that this select group represents a set of misfolded membrane protein stress-responders and includes: 1) PRE2, which encodes the chymotrypsin-like subunit of the proteasome; 2) HSP30, which encodes a membrane-associated heat shock protein that regulates the yeast plasma membrane H ϩ -ATPase (102, 121); 3) BTN2, which encodes a v-SNARE Table 3. Misfolded membrane proteins induce a discrete set of genes required for endosome-to-Golgi trafficking (72) and interacts with the Sis1 (Hsp40) and Hsp42 (sHsp) molecular chaperones (95); and 4) HCH1, which encodes an Hsp90 partner, activates the chaperone's ATPase activity, and regulates cellular sensitivity to Hsp90 inhibitor (5,89,122). Like Hsp90, Hch1 is also heat shock responsive, and Hsp90 stabilizes both CFTR and Ste6* in yeast and human cells (88,111,167).…”
Section: Kir21 Cftr Enacmentioning
confidence: 99%